Perspectives on Food Security: A Gender Based Comparison of Rural Households in South East Nigeria (Global Journal of Human-Social Science, 2014)
Household food insecurity remains a persistent and pressing social concern despite the economic gains that Nigeria has made over the years.The study focused on identifying the perception of male and female headed households about food security; the gaps in calories supplied as well as factors that interact to influence food supply.Primary data was collected using the farming and rural systems approach to randomly select and interview 120 households but a subsection of the sample is the basis for this study. Descriptive statistics was used to describe the perceptions about food security and gaps in calories supplied. Two-stage Least Square regression and the General Linear Model were used to determine the factors that influence calorie supply to the households as well as the influence exacted by the interaction of those factors.
Keywords: perspectives; food security; male/female headed households